Calculation of flow separation in a retarded boundary-layer over a moving continuous sheet. (16th November 2021) - Mehmood, Ahmer; Shah, Babar Hussain; Usman, Muhammad; Raza, Iqrar
Abstract: Theoretical investigations of fundamental boundary-layer flows are always given prime importance in the field of boundary-layer theory. In particular, among the boundary-layer flows occurring on planner geometries, importance had been given to the flows occurring over the surfaces of finite length. The boundary-layer flows due to moving continuous surfaces were introduced about half a century later to the famous Blasius flow. Unfortunately, no significant attention had been given to these flows with regard to the investigation of boundary-layer properties in these flows. Consequently, a great gap has been created between these two important categories of boundary-layer flows. It is a matter of fact that the flows due to moving continuous surfaces are richer in physics; offer favorable impact, and involve interesting technological applications. One of the important hallmarks of these flows is that they offer a significantly increased wall skin-friction as compared to the flows over surfaces of finite length. Therefore these flows appear to be profitable in situations that are more vulnerable to flow separation. To explore this fact the current study considers a variety of retarded wall velocities to calculate the delay in flow separation for the flows due to moving continuous surfaces in comparison to those occurring on a surface of finite length. It is observed that in the flows due to a moving continuous surface the flow separation is greatly delayed in comparison to the flows over surfaces of finite length. Moreover, the role of wall suction velocity, in this regard, is to be further amplified in these flows. Overall, it is concluded that the continuous surfaces are more useful in order to delay flow separation as compared to the surfaces of finite length.